Impact of COVID-19 on Pediatric Gastroenterology Fellow Training in North America. Issue 1 (July 2020) - Mallon, Daniel; Pohl, John F.; Phatak, Uma P.; Fernandes, Melissa; Rosen, John M.; Lusman, Sarah S.; Nylund, Cade M.; Jump, Candi S.; Solomon, Aliza B.; Srinath, Arvind; Singer, Andrew; Harb, Rula; et al.
ABSTRACT: Background: The COVID-19 pandemic has drastically changed healthcare systems and training around the world. The Training Committee of the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition sought to understand how COVID-19 has affected pediatric gastroenterology fellowship training. Methods: A 21 question survey was distributed to all 77 pediatric gastroenterology fellowship program directors (PDs) in the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition program director database via email on April 7. Responses collected through April 19, 2020 were analyzed using descriptive statistics. Results: Fifty-one of 77 (66%) PDs from the United States, Canada, and Mexico responded to the survey. Forty-six of 51 (90%) PDs reported that they were under a "stay-at-home" order for a median of 4 weeks at the time of the survey. Two of the 51 (4%) programs had fellows participating in outpatient telehealth before COVID-19 and 39 of 51 (76%) at the time of the survey. Fellows stopped participating in outpatient clinics in 22 of 51 (43%) programs and endoscopy in 26 of 51 (52%) programs. Changes to inpatient care included reduced fellow staffing, limiting who entered patient rooms, and rounding remotely. Fellows in 3 New York programs were deployed to adult medicine units. Didactics were moved to virtual conferences in 47 of 51 (94%) programs, and fellows used various online resources. Clinical research and, disproportionately, bench research were restricted. Conclusions: This report provides early information of the impact of COVID-19 on pediatric fellowship training. Rapid adoption of telehealth and reduced clinical and research experiences were important changes. Survey information may spur communication and innovation to help educators adapt. Abstract : Supplemental Digital Content is available in the text